KOMUNIKASI ORGANISASI PADA DINAS KEBUDAYAAN PROVINSI BALI - Gusti Ayu Widiani; Moch Noor; I Made Gede Ray Misno (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Communication is an important element in the survival of a society or organization. The role of communication in an organization can create a conducive working relationship in achieving organizational goals, create harmonious cooperation, and create mutual understanding between employees and leaders so as to form social conditions that can motivate employees to improve work productivity. Therefore, the purpose of this study was to find out how the organizational communication took place at the Bali Provincial Cultural Office. This study used 30 samples as primary data, which were analyzed quantitatively. The average score of respondents' answers in terms of downward communication or communication from leaders to subordinates is 97.3. Then, the average score of respondents' answers in terms of communication from subordinates to superiors is 77.8. Finally, the average score of respondents' answers in terms of horizontal communication or communication between employees at the same level/echelon is 18. Based on these scores, the writers conclude that good organizational communication is evident in Bali Provincial Culture Service.